Homicidal arsenic poisoning. (July 2015) - Duncan, Andrew; Taylor, Andrew; Leese, Elizabeth; Allen, Sam; Morton, Jackie; McAdam, Julie
The case of a 50-year-old man who died mysteriously after being admitted to hospital is reported. He had raised the possibility of being poisoned prior to his death. A Coroner's post-mortem did not reveal the cause of death but this was subsequently established by post-mortem trace element analysis of liver, urine, blood and hair all of which revealed very high arsenic concentrations.